The Relationship of Problem Based Learning with Student Learning Motivation in Mathematics Subjects - Nilawati Putri Ramdhani (Universitas Sebelas Maret, 2022)
This article as a literature review aims to determine the relationship between problem based learning and student motivation in mathematics. At this time, many teaching and learning activities still use the conventional model, where the teacher dominates the learning process. In addition, the learning model used by the teacher in learning is less interesting & varied, so students are less enthusiastic about learning. Students themselves are passive, only receiving the information conveyed by the teacher. The process of learning mathematics in elementary schools requires active and meaningful interactions between teachers and students. To be able to create an active learning process, teachers need to increase creativity in learning, one of which is by holding variations in teaching so as to create an active and fun learning process so that students can be motivated in learning. One of them can use a mathematics learning model that can stimulate students' curiosity in learning, one of which is by using a problem-based learning model.